2022
DOI: 10.3389/fimmu.2022.1027385
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy for the treatment of multiple myeloma

Abstract: Despite advances in treatment for multiple myeloma, the majority of patients ultimately develop relapsed disease marked by immune evasion and resistance to standard therapy. Immunotherapy has emerged as a powerful tool for tumor-directed cytotoxicity with the unique potential to induce immune memory to reduce the risk of relapse. Understanding the specific mechanisms of immune dysregulation and dysfunction in advanced myeloma is critical to the development of further therapies that produce a durable response. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 144 publications
0
9
0
Order By: Relevance
“…Currently, some of chimeric antigen receptor (CAR)-T cell therapies and vaccines using peptides are being tested in clinical trials and being used in MM treatments, especially for patients with relapse or refractory cancer 57 . However, there is still need for further development of combinatorial antigen approaches for more e cient and speci c therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, some of chimeric antigen receptor (CAR)-T cell therapies and vaccines using peptides are being tested in clinical trials and being used in MM treatments, especially for patients with relapse or refractory cancer 57 . However, there is still need for further development of combinatorial antigen approaches for more e cient and speci c therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, some of chimeric antigen receptor (CAR)-T cell therapies and vaccines using peptides are being tested in clinical trials and being used in MM treatments, especially for patients with relapse or refractory cancer 88 . However, there is still need for further development of combinatorial antigen approaches for more e cient and speci c therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Stromal-cell-induced MM growth was abrogated by blocking PD1/PD-L1 and enhanced in combination with lenalidomide ex vivo [ 149 ]. Durvalumab and nivolumab, PD-1 inhibitors, are being tested in combination with other compounds such as IMiDs, daratumumab, and venetoclax (Bcl-2 inhibitor) [ 118 , 150 ]. A phase Ib KEYNOTE-013 trial (NCT01953692) for pembrolizumab, a PD-1 inhibitor, in RRMM patients showed 2.7 months PFS and 20.2 months OS after a median follow-up of 19.9 months [ 151 ].…”
Section: The Development Of Immunotherapies In MMmentioning
confidence: 99%